Upaya Hukum dan Perlindungan terhadap Istri dalam Perkara Suami Mafqud - Muthia Hartati; Muhammad Yunus (Jurnal Riset Hukum Keluarga Islam, 2022)
Abstract. The missing husband (mafqud / unseen) certainly creates new problems in the household, in the implementation of rights and obligations for husband and wife. The loss of a husband creates an unclear status for the wife who is left behind, how long the wife has to wait until she can file a divorce suit, and whether the marriage can be terminated or not. The purpose of this study is to find out how the rules for unseen divorce and the determination of mafqud according to positive law and Islamic law, and to find out how to analyze the mafqud case in case Number 154/Pdt.G/2021/PA.Smdg in the Sumedang Religious Court according to positive law and Islamic law. This research was conducted using a normative legal research method using qualitative analysis that describes legal issues that have been written in the Qur'an and al-Hadith as well as the Act, the opinions of scholars and legal experts so that several opinions emerge with various similarities and differences. The primary data of this research comes from the decision of the Religious Court Number 154/Pdt.G/2021/PA.Smdg, the results of the judge's interview, Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning Marriage, based on the results of research conducted The results obtained in this thesis are that a wife whose husband is mafqud for a long period of time may file for divorce because her rights are not fulfilled. In article 19 PP No. 9 of 1975, the minimum time limit for a wife to file for divorce because her husband is missing is two years, while according to Imam Malik and Imam Ahmad bin Hambal it is four years. Abstrak. Suami yang hilang (mafqud/ghaib) tentunya menimbulkan persoalan baru dalam rumah tangga, dalam pelaksanaan hak dan kewajiban bagi suami istri. Hilangnya suami menimbulkan ketidakjelasan status bagi istri yang ditinggalkan, berapa lama istri harus menunggu hingga dapat mengajukan gugatan perceraian, dan apakah perkawinannya dapat diputus atau tidak. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana aturan cerai ghaib dan penentuan mafqud menurut hukum positif dan hukum Islam, serta untuk mengetahui bagaimana analisis kasus mafqud dalam perkara Nomor 154/Pdt.G/2021/PA.Smdg di Pengadilan Agama Sumedang menurut hukum positif dan hukum Islam. Penelitian ini dilakukan menggunakan metode penelitian hukum normatif menggunakan analisis kualitatif yang memaparkan persoalan hukum yang telah tertulis dalam al-Qur’an dan al- Hadis serta Undang-Undang, pendapat Para Ulama dan ahli hukum sehingga muncul beberapa pendapat dengan berbagai persamaan dan perbedaan. Data primer penelitian ini bersumber dari putusan Pengadilan Agama Nomor 154/Pdt.G/2021/PA.Smdg, hasil wawancara hakim, Undang-Undang Nomor 16 Tahun 2019 tentang perubahan atas Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, berdasarkan hasil penelitian yang didapat dalam skripsi ini adalah bahwa seorang istri yang suaminya mafqud dalam kurun waktu yang lama, boleh mengajukan cerai disebabkan hak-haknya tidak terpenuhi. Dalam pasal 19 PP No. 9 tahun 1975 waktu batas minimal istri boleh mengajukan cerai karena suaminya hilang adalah dua tahun sedangkan menurut Imam Malik dan Imam Ahmad bin Hambal adalah empat tahun.